Substratos para o crescimento de mudas de Trema micrantha (L.) Blumes - Nóbrega, Rafaela Simão Abrahão (2010)
This study aimed at assessing the effects of solid urban waste and liming in the initial growth of Trema micrantha (L. Ulmaceae) seedlings in tubes. To conduct the study, an experiment was installed in a greenhouse, displayed in a completely randomized design, in a factorial scheme 2x5, in samples of Red Distroferric Latossol (Oxisol) with and without liming and five proportions of urban waste compost: 0; 10; 20; 40 and 80% v/v, without complementary fertilization, with five replications. 120 days after the beginning of the experiment, the seedlings were collected to determine: shoot dry matter, root dry matter and total dry matter, as well as the relation between shoot dry matter and root dry matter. There was no significant effect of lime nor its interaction with waste compost in the parameters evaluated. Waste compost increased seedlings shoot dry matter production. Such effects varied according to the proportions of compost used. The average proportion was 54.7% of solid urban waste and 45.3% of Red Distroferric Latossol (Oxisol), which favors dry matter production of Trema micrantha (L. Ulmaceae) seedlings.